2016
DOI: 10.5114/wiitm.2016.60665
|View full text |Cite
|
Sign up to set email alerts
|

Patient comfort during flexible and rigid cystourethroscopy.

Abstract: IntroductionCystourethroscopy (CS) is an endoscopic method used to visualize the urethra and the bladder.AimIn this study, we prospectively evaluated pain in men undergoing cyclic cystoscopic assessment with rigid and flexible instruments after transurethral resection of bladder tumor (TURB).Material and methodsOne hundred and twenty male patients who were under surveillance after a TURB procedure due to urothelial cell carcinoma and who had undergone at least one rigid cystourethroscopy in the past were enrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 8 publications
2
25
0
6
Order By: Relevance
“…Similar to our previous study, it was shown that pain sensation remembered by patients from the previous CS is high (mean 5.7 ± 2.4 points) often reaching ten points, which is quoted as “unbearable pain” [ 5 ]. The level of the recalled pain was not related to the patients’ age and HADS anxiety level; however, it was positively associated with depression symptoms.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Similar to our previous study, it was shown that pain sensation remembered by patients from the previous CS is high (mean 5.7 ± 2.4 points) often reaching ten points, which is quoted as “unbearable pain” [ 5 ]. The level of the recalled pain was not related to the patients’ age and HADS anxiety level; however, it was positively associated with depression symptoms.…”
Section: Discussionsupporting
confidence: 81%
“…Rigid tools offer good irrigant flow and handiness along with wide working channel lumen. Flexible cystoscopes provide more possibilities for patient positioning, enable easy course over an elevated bladder neck or median lobe, facilitate full inspection of the bladder mucosa, and, what is the most important, significantly improve patient comfort [ 5 ]. Urologists often repeat an argument that rigid cystoscopes offer a better image quality.…”
Section: Introductionmentioning
confidence: 99%
“…8 Sin embargo, se ha demostrado que tanto los dispositivos rígidos como los flexibles tienen la misma eficacia para identificar tumores en la vejiga. 9 Aunque la cistoscopia flexible aumenta la tolerancia, especialmente en pacientes masculinos, el dolor sigue siendo inevitable durante la misma. El uso de técnicas anestésicas, incluida la lubricación uretral, el pretratamiento con narcóticos intramusculares, la evaluación del volumen de lidocaína, inyección intrauretral de gel de lidocaína enfriada, inhalación de óxido nitroso, la administración lenta de anestésicos locales y la estimulación eléctrica nerviosa transcutánea, se han descrito para disminuir la incomodidad del procedimiento en pacientes masculinos.…”
Section: La Cistoscopia Y El Dolorunclassified
“…Imaging 6 , 7 , and urinary marker tests 8 , 9 are complementary, and none has yet become an acceptable alternative to cystoscopy 10 . Flexible cystoscopy under local anaesthesia is associated with better patient acceptance, particularly in men 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%